Cover Image, Volume 5, Issue 3. (14th April 2016) - Steinkraus, Bruno R.; Toegel, Markus; Fulga, Tudor A.
Abstract : The cover image, by Tudor Fulga et al., is based on the Advanced Review Tiny giants of gene regulation: experimental strategies for microRNA functional studies, DOI: 10.1002/wdev.223 . Abstract : The cover image, by Tudor Fulga et al., is based on the Advanced Review Tiny giants of gene regulation: experimental strategies for microRNA functional studies, DOI: 10.1002/wdev.223 .